Enhanced Antitumoral Activity and Photoacoustic Imaging Properties of AuNP‐Enriched Endothelial Colony Forming Cells on Melanoma. Issue 4 (21st December 2020) - Armanetti, Paolo; Chillà, Anastasia; Margheri, Francesca; Biagioni, Alessio; Menichetti, Luca; Margheri, Giancarlo; Ratto, Fulvio; Centi, Sonia; Bianchini, Francesca; Severi, Mirko; Traversi, Rita; Bani, Daniele; et al.
Abstract: Near infrared (NIR)‐resonant gold nanoparticles (AuNPs) hold great promise in cancer diagnostics and treatment. However, translating the theranostic potential of AuNPs into clinical applications still remains a challenge due to the difficulty to improve the efficiency and specificity of tumor delivery in vivo as well as the clearance from liver and spleen to avoid off target toxicity. In this study, endothelial colony forming cells (ECFCs) are exploited as vehicles to deliver AuNPs to tumors. It is first demonstrated that ECFCs display a great capability to intake AuNPs without losing viability, and exert antitumor activity per se. Using a human melanoma xenograft mouse model, it is next demonstrated that AuNP‐loaded ECFCs retain their capacity to migrate to tumor sites in vivo 1 day after injection and stay in the tumor mass for more than 1 week. In addition, it is demonstrated that ECFC‐loaded AuNPs are efficiently cleared by the liver over time and do not elicit any sign of damage to healthy tissue. Abstract : The findings herein firmly establish gold nanoparticle (AuNP)‐loaded endothelial colony forming cells (ECFCs) as excellent theranostic agents that can be tracked with simple imaging methods and display inherent antitumor properties. The study highlights their capacity to migrate to tumor sites in vivo 1 day after injection and remain in the tumor mass for more than 1 week.